To construct a polynomial function from the given zeros and their multiplicities, we need to follow these steps:
-
Identify the zeros and their multiplicities:
- Zero \(x = 4\) with multiplicity \(1\)
- Zero \(x = -2\) with multiplicity \(3\)
-
Write the polynomial as a product of factors based on these zeros:
- The factor for the zero \(x = 4\) is \((x - 4)\)
- The factor for the zero \(x = -2\) is \((x + 2)\), and since it has a multiplicity of \(3\), it will be raised to the third power: \((x + 2)^3\)
-
Combine these factors into one polynomial: \[ f(x) = (x - 4)(x + 2)^3 \]
Now, let's compare this with the answer choices:
a. \( f(x) = (x + 4)(x - 2) \) - Not correct. b. \( f(x) = (x - 4)(x + 2) \) - Not correct (missing the third power). c. \( f(x) = (x - 4)(x + 2)^3 \) - Correct. d. \( f(x) = (x + 4)(x - 2)^3 \) - Not correct.
Therefore, the correct function Jaime should write is:
c. \( f(x) = (x - 4)(x + 2)^3 \).